E.P. Fager and Viola Suess at Dearborn Chemical Company facility in Chicago, Illinois - Dearborn Chemical Company (1927)
General view of employees E.P. Fager and Viola Suess at work in an office at the Dearborn Chemical Company's 35th Street laboratory facility located in Chicago, Illinois. An unidentified chemist, visible through the doorway, is depicted at work in a laboratory adjacent to the office. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers and cooling towers.
Keywords: Employees; Chemical industry; Laboratories; Water purification chemicals industry; Corporations; Women employees; Dearborn Chemical Company; Seuss, Viola; Fager, E.P.